Konkurencyjność banków spółdzielczych w obsłudze klientów indywidualnych– metodologiczne problemy doboru próby badawczej - Snarski, Paweł (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The paper aims at analyzing selected sampling methods, with particular attention to the needs of the planned exploration of the competitiveness of cooperative banks compared to commercial banks. It was found that an adequate sample of research is crucial to obtain representative results. Mistakes in the selection of the sample may give differences between the distribution of characteristics in the sample and the general population. In this situation the hypothesis may remain unresolved.